2019
DOI: 10.1653/024.102.0125
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the Pollination Biology of Encyclia tampensis, the Commercially Exploited Butterfly Orchid, and Prosthechea cochleata, the Endangered Clamshell Orchid, in South Florida

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Unfortunately, pollination studies in Prosthechea are scarce, with only reports of floral visitors such as bees ( P. cochleata , P. vespa ) and wasps ( P. baculus ), as well as some spontaneous self‐pollinating forms in various species ( P. boothiana , P. chacaoensis (Rchb.f.) W.E.Higgins, P. cochleata , P. cretacea (Dressler & G.E.Pollard) W.E.Higgins, P. vespa ) being documented in literature (Dodson, 1962; Van der Pijl & Dodson, 1966; Dressler & Pollard, 1976; Dressler, 1981; Catling, 1990; Quiroga & al., 2010; Ray & al., 2019; Ackerman & al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, pollination studies in Prosthechea are scarce, with only reports of floral visitors such as bees ( P. cochleata , P. vespa ) and wasps ( P. baculus ), as well as some spontaneous self‐pollinating forms in various species ( P. boothiana , P. chacaoensis (Rchb.f.) W.E.Higgins, P. cochleata , P. cretacea (Dressler & G.E.Pollard) W.E.Higgins, P. vespa ) being documented in literature (Dodson, 1962; Van der Pijl & Dodson, 1966; Dressler & Pollard, 1976; Dressler, 1981; Catling, 1990; Quiroga & al., 2010; Ray & al., 2019; Ackerman & al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The generated trees, either of BI or MP analysis, were visualized and preliminarily edited in FigTree v.1.4 (Rambaut, 2012). The schematic figure of data partition trees presented in suppl.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…This possibility requires further evaluation through physiological studies, as some species have shown the ability to cope with climate change effects due to inherent phenotypic plasticity in physiological traits [ 56 ] or rapid niche shifts [ 57 , 58 ]. However, it is unlikely that niche shifts in P. mariae would occur within just five decades, given the limited information available on the genus, which suggests relatively small population sizes and annual generation times [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…diandra and var. triandra, being the focus of this paper (Ray et al 2019; Belfort-Oconitrillo and Pupulin 2020). Horticulturally var.…”
Section: Introductionmentioning
confidence: 98%
“…triandra is not known to form specialized relationships with native pollinators in Florida, and insect visitations for var. triandra are very rare (Ray et al 2019). Triandrous individuals have additional anthers on the column and increased pollen load that facilitates sel ng, resulting in local endemism throughout the range.…”
Section: Introductionmentioning
confidence: 99%